REVIEW OF THE HOME OWNERSHIP LOAN (KPR) PROCEDURE AT BANK BTN KC TASIKMALAYA - Iman Nugraha, Cecep; Andi Usmar (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to review the mortgage lending process in a bank, focusing on procedures, requirements, and challenges faced by both the bank and customers. The research background is based on the author's internship experience at the bank, providing an opportunity to gain in-depth insights into the mortgage approval mechanism from a practical perspective. This study employs a qualitative method, utilizing interviews with bank employees involved in the mortgage application process and literature studies related to banking policies. The findings reveal that mortgage approval involves a comprehensive evaluation of the borrower's financial capability, including credit analysis and compliance with banking regulations. Additionally, several challenges were identified, such as the lengthy administrative process and credit risk factors that the bank must consider. The conclusion of this study emphasizes that mortgage lending requires a balance between the bank's interests and customer needs, necessitating innovations in procedures and service optimization to improve process efficiency.